EVALUATION OF ANTIBIOTICS UTILIZATION AND DOSING FOR MANAGEMENT OF PATIENTS WITH CHRONIC KIDNEY DISEASE IN AN INDONESIAN HOSPITAL - AZIZAH, NASUTION; AZHAR, SYED SULAIMAN SYED; AKMAL, SHAFIE ASRUL (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Provision of antibiotics to patients with chronic kidney disease (CKD) without dosage adjustment could result in complicated problems including progression of kidney damage. This study analyzed utilization and dose rationality of antibiotics administered to stage 4 and 5 CKD patients in Haji Adam Malik (HAM) hospital, Indonesia. Methods: This retrospective cohort study was conducted on six-month JAMKESMAS database (n=80). Inclusion criteria were in-patients received antibiotics and GFR of ≤30 mL/min/1.73 m2. Exclusion criteria were patients with cancer and Human Immunodeficiency Virus and below 18 years old. Characteristics of the study population were descriptively analyzed. Antibiotics utilization was determined by assessing unit numbers of the provided antibiotics. Dose rationality of the antibiotics was analyzed by referring to dose recommended in literatures based on the patients'creatinine clearance. Proportion of the patients received irrational doses was analyzed applying frequency analysis. All statistical analyses were performed using SPSS program version 19. Results: Mean age of the CKD patients was 47.08 (SD = 13.80) years. There were more male patients (66%) compared to female, p = 0.003. There were more patients with CKD stage 5 (83%) compared to CKD stage 4, p = <0.001. Eleven classes of antibiotics were provided to CKD patients of which 9 had irrational doses received by 34% of the patients. Ceftriaxone, ciprofloxacin, ceftazidime, cefadroxyl, and amoxicillin had the highest irrational dose incidence. Conclusion: Incidence of irrational antibiotics dosage provided to the CKD patients was still high. Keywords: CKD, Infection, Antibiotics dosing